Tandem tyrosine phosphosites in the Enteropathogenic Escherichia coli chaperone CesT are required for differential type III effector translocation and virulence. Issue 5 (30th March 2018) - Runte, Cameron S.; Jain, Umang; Getz, Landon J.; Secord, Sabrina; Kuwae, Asaomi; Abe, Akio; LeBlanc, Jason J.; Stadnyk, Andrew W.; Kaper, James B.; Hansen, Anne‐Marie; Thomas, Nikhil A.
Summary: Enteropathogenic Escherichia coli (EPEC) use a type 3 secretion system (T3SS) for injection of effectors into host cells and intestinal colonization. Here, we demonstrate that the multicargo chaperone CesT has two strictly conserved tyrosine phosphosites, Y152 and Y153 that regulate differential effector secretion in EPEC. Conservative substitution of both tyrosine residues to phenylalanine strongly attenuated EPEC type 3 effector injection into host cells, and limited Tir effector mediated intimate adherence during infection. EPEC expressing a CesT Y152F variant were deficient for NleA effector expression and exhibited significantly reduced translocation of NleA into host cells during infection. Other effectors were observed to be dependent on CesT Y152 for maximal translocation efficiency. Unexpectedly, EPEC expressing a CesT Y153F variant exhibited significantly enhanced effector translocation of many CesT‐interacting effectors, further implicating phosphosites Y152 and Y153 in CesT functionality. A mouse infection model of intestinal disease using Citrobacter rodentium revealed that CesT tyrosine substitution variants displayed delayed colonization and were more rapidly cleared from the intestine. These data demonstrate genetically separable functions for tandem tyrosine phosphosites within CesT. Therefore, CesT via its C‐terminal tyrosine phosphosites, has relevant roles beyond typical type III secretion chaperones that interact and stabilize effector proteins. Abstract : Pathogens with type III secretion systems (T3SS) absolutely require dedicated chaperone proteins to mediate efficient effector protein injection into host cells during infection. In this study, we implicate tandem tyrosine phosphosites of CesT in differentially regulating effector secretion and contributing to intestinal disease. These findings expand the functional importance of CesT in context of bacterial pathogenesis, revealing an unexpected phosphosite specificity for a T3SS chaperone.